Abordagem inteligente para o uso racional de um recurso compartilhado utilizando blockchain - Sestrem, Evandro (2021)
To solve the problem of the “tragedy of the commons”, this work presents an intelligent approach to managing and controlling the use of a resource shared by a community and, at the same time, encouraging the realization of positive actions that can be done in exchange for the use of these resources. For this, several metaheuristics are studied and the TLBO (Teaching–Learning Based Optimization) is chosen to be used in conjunction with the concepts of economics “architecture of choices” to prioritize the choice of certain positive actions. Our approach makes use of blockchain to keep data decentralized. The implementation of the approach in a real application is presented.A simulator developed to carry out experiments in different scenarios is also presented, showing that the presented approach is generic and can be used in different applications. The results found when running 8 scenarios in the simulator are presented, and in each scenario 6 types of roulettes were applied to reproduce the behavior of a community. It can be seen how it is possible to prioritize the actions selected by the members of a community where the approach is applied.